A Study Of Total Preventive Maintenance (TPM) At Zircom Diecast (M) Sdn. Bhd. - Seerangan, Gunasegeran (2004)
This purpose of the study was empirically to examine the success of the Total Preventive Management program at ZirCom Diecast (M) Sdn. Bhd that was implemented about two years ago with so much of enthusiasm by the management.